Strategi Pembentukan Karakter Islami Siswa Sekolah Dasar di Masa Transisi Covid-19 Menuju Aktivitas New Normal - Muh Khaerul Ummah BK; Hamna Hamna (Jurnal Bidang Pendidikan Dasar, 2022)
This study aims to determine the strategy of Islamic religious education teachers in shaping the Islamic personality of students in elementary schools. This study used a qualitative descriptive method involving Islamic religious education teachers, head master and representatives of students' parents as research informants. The results showed that the Islamic religious learning strategy oriented to the formation of the Islamic character of students was carried out adaptively in accordance with local government policies related to learning strategies during the pandemic and the need for the presence of role models to shape students' Islamic personalities. Various solutions that can be applied by Islamic religious education teachers in an effort to form students' Islamic character during pandemic are to apply learning activity scheduling strategies, apply student learning discipline strategies and strengthen exemplary and optimize learning assistance from students' parents.